Posthuman fictions, queer ecofeminism and multispecies relations in the movies Princess Mononoke, Annihilation and the comic Monstress - Retana-Bustamante, Andy (2026)
Objective: This article explores how speculative fiction can imagine multispecies forms of life from an ecofeminist, queer, and posthuman perspective. Through a comparative analysis of Princess Mononoke (Miyazaki, 1997), Annihilation (Garland, 2018), and the comic Monstress (Liu & Takeda, 2019), the study examines how these narratives depict entangled relationships between bodies, species, and systems of organization within contexts of ecological collapse and systemic violence. Methodology: The article employs an analytical-interpretative methodology grounded in queer ecofeminism, posthumanism, and multispecies studies. From this perspective, it analyzes the forms of coexistence, agency, and transformation that emerge beyond anthropocentric paradigms, approaching fiction as a critical and speculative site for reimagining life and relationality. Results: Findings reveal that these works construct posthuman imaginaries in which agency is distributed among human and nonhuman actors. Rather than portraying ecological catastrophe as a definitive rupture, these fictions treat it as a space of possibility for metamorphosis and renewal. Monstrosity, hybridity, and ruin appear as forces that destabilize the boundaries between nature and culture, opening paths to rethink corporeality and interspecies interdependence. Conclusions: Ultimately, the article argues that speculative fiction offers a critical and poetic framework to fabulate new alliances among species and to conceive relational modes of existence that resist anthropocentric logic. These narratives not only expose ecological collapse but also reconfigure it as fertile ground for imagining alternative futures for the Latin American context, by cohabitating in the world beyond moderni, anthropocentric and extractivist logics